Optimization of the sustainability during the refurbishment operation of a residential building - Mateus, Isabel (2013)
Most of the existing buildings have high resources consumption and low indoor environmental quality, leading to the unsustainability of the built environment. Being aware of this reality and based in the European goal to achieve Nearly-Zero Energy consumption standard in buildings, it is urgent to define guidelines that could support the sustainable refurbishment design since the earlier stages. This paper intends to illustrate the process of sustainable building refurbishment, supported by different guidelines applied to a case study. To achieve this goal the definition and evaluation of a group of procedures to be implemented, and a cost-benefit analysis applied to a case study was performed, having as final goal its sustainability optimization.